Comparison Study of Red Blood Cells and their Characteristics in Female Camels and their Male Calves in Libya - Altief, Tarek A.S.; Amir, Moneam A.; Sabir, Salem A.; Amaizik, Salem A. (Al-Mukhtar Journal of Sciences, 2022)
The study was conducted to comparison study of red blood cells and their characteristics in female camels and their male calves in Libya in the central region of Libya for a period of one year on three camels, male calves were selected according to birth. (MCH) and (MCHC) were evaluated in the blood of the mothers, and they were found to be significantly higher (P